Enhancing Adaptive Reasoning Ability In Senior High School Students Using The Guided Inquiry Method: A Quasi-Experimental Study - Jatisunda, Mohamad Gilar; Nahdi, Dede Salim; Cahyaningsih, Ujiati; Rasyid, Abdur (Journal of Multidisciplinary Research and Development, 2024)
This study aims to evaluate the effect of the guided inquiry method on students' adaptive reasoning ability at the secondary school level. With a quasi-experimental design using a Nonequivalent Control Group Design, class X IPS 1 applied guided discovery, while class X IPS 2 was the control with conventional learning. Adaptive reasoning ability data were obtained from pretests and posttests, then tested using paired-sample T-test. The results showed a significant increase in the experimental class (N-Gain: 0.64) compared to the control class (N-Gain: 0.55), with a significance value of 0.009. This finding indicates that the application of the guided discovery method has a more significant positive impact on improving students' adaptive reasoning ability when compared to conventional learning. The implication is that teachers and education practitioners can consider using this method to improve the quality of mathematics learning at the secondary school level. Further studies could explore specific aspects of this method and its long-term impact on student achievement